The multifaceted roles of common gut microbiota in immune checkpoint inhibitor-mediated colitis: From mechanism to clinical application - Han, Xu; Zang, Dan; Liu, Dan; Chen, Jun (Frontiers in Immunology, 2022)
With the arrival of the era of tumor immunotherapy, Immune Checkpoint Inhibitors have benefited countless tumor patients. However, the emergence of Immune-Related Adverse Events, especially Immune Checkpoint Inhibitor-Mediated Colitis (IMC), has become an important obstacle to immunotherapy. Therefore, it is very important to clarify the mechanism and influencing factors of IMC. The effect of gut microbiota on IMC is gradually becoming a research hotspot. Gut microbiota from different phyla can affect IMC by regulating innate and acquired immunity of tumor patients in various ways. In this review, we make a systematic and comprehensive introduction of the effect of gut microbiota on IMC. Through understanding the specific effects of gut microbiota on IMC, and then exploring the possibility of reducing IMC by regulating gut microbiota.